Jejunal intramural haematoma in a captive African lion (Panthera leo). Issue 1 (25th December 2022) - Butcher, Richelle G.; Lenting, Baukje; Clarke, Alison S.; Buckle, Kelly; Gans, Cristina
Abstract: A 19‐year‐old, entire, female, captive African lion ( Panthera leo ) presented acutely for reduced appetite and lethargy. Bloodwork revealed a poorly regenerative anaemia, hypoalbuminaemia and monocytosis. Ultrasound indicated the presence of a peri‐renal mass, but advanced imaging techniques were unavailable at the time. Minimal clinical improvement was seen with supportive treatment, and euthanasia was elected 11 days after presentation. Postmortem examination revealed an intramural intestinal haematoma of the jejunum with serosal haemorrhage and haemoabdomen, and a peri‐renal mass. Histology showed that the peri‐renal mass was an adrenal cortical carcinoma. The underlying cause of the intramural haematoma was not determined, but it was considered the probable cause for the clinical decline of this animal. Intramural intestinal haematoma is an uncommon entity in veterinary species, and has not been reported in any members of Felidae. This is the first documented case of an intramural intestinal haematoma in an African lion.